Simulation of PID and fuzzy logic controller for the newly developed switched reluctance motor program - Ahmad Shukri, Fazil Rahman; Mohd. Nasir, Taib (Universiti Teknologi MARA (UiTM), 2009)
Organized by Universiti Teknologi MARA (UiTM), 16-17 July 2002 at Blue Wave Hotel, Shah Alam, Selangor.